EU Foreign Policy in the Eastern Partnership : Case Study of the Republic of Moldova - Suhan, Dorin (2021)
With the European Union's enlargement to Central and Eastern Europe, the EU's foreign policy priorities have changed accordingly. As its border moved east, an adaptation was needed, even a redefinition of the institutional framework and policies aimed at its immediate neighborhood. In this context, the European Neighborhood Policy (ENP) has emerged. Through its geographical location, the Republic of Moldova is integrated into a conjuncture of several geostrategic interests, which forces it to respond promptly to the diversity of political issues involved. Crossing a turbulent historical path, it has often been invoked as an element of compromise and satisfaction of the political objectives claimed by various external actors in regional disputes. The most obvious problem that Moldova faced and continues to face was assuming a position and belonging to the eastern vector intersection with the western one. This thesis aims to show that the Eastern Partnership represents the “buffer zone” between these two powerful actors in Europe. For both, the region has a great geostrategic reason; by influencing these countries, Russia or the EU can tip the balance of power in their favor on the European continent. The thesis will prove that the EU has imposed itself as a strong economic partner in this region by defaming Russia, which has been the main economic partner in this area for more than 25 years, but politically, the EU has failed to influence the internal policy of these countries.